Pengaruh Uji Kelaikan Ground Support Equipment dan Kinerja Ground Support Operator dalam Mendukung Keselamatan Operasional di Sisi Udara Bandar Udara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - BELLA FADHILAH, NOVIANA; Fauziah , Syifa (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The implementation and effectiveness of the Ground Support Equipment (GSE) airworthiness test procedure were studied in this study. The selected research location was Sultan Aji Muhammad Sulaiman Sepinggan Airport, Balikpapan. The independent variables reviewed were the Ground Support Equipment airworthiness test and the performance of the Ground Support Operator, while the dependent variable was operational safety on the airside. The study included the presence or absence of the influence of these variables, either partially or simultaneously. If there is, how big is the influence. A quantitative approach was used in analyzing 60 questionnaire data samples, which were distributed among employees of the AMC and AVSEC units. The quantitative technique used descriptive analysis, validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear analysis test, F test, T test, and determination coefficient analysis. Data processing was carried out in SPSS software version 23. The results of the descriptive analysis showed that the average of the airworthiness test variable was 4.38, the performance variable was 4.12 and the safety variable was 3.70. The results of the hypothesis testing show that H0 is rejected while H1 is accepted. The coefficient of determination is 0.217.